2015
DOI: 10.4103/1119-3077.151046
|View full text |Cite
|
Sign up to set email alerts
|

Bonding performance of two newly developed self-adhering materials between zirconium and dentin

Abstract: GC EQUIA material showed a higher shear bond strength value than other resin materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
2
0
0
Order By: Relevance
“…The authors report that the three adhesive primer components (a silane component, a sulphide-containing adhesion promoter and a phosphate-containing adhesion promoter) do not negatively influence the durability of the system (Azimian et al, 2012). Moreover, the results of our study confirm the clinical evidence that the presence of phosphate monomers associated with air-abrasion procedures can provide more stable adhesion of resin cements to zirconia in oral conditions (Attia and Kern, 2011;Cebe et al, 2015).…”
Section: Discussionsupporting
confidence: 84%
“…The authors report that the three adhesive primer components (a silane component, a sulphide-containing adhesion promoter and a phosphate-containing adhesion promoter) do not negatively influence the durability of the system (Azimian et al, 2012). Moreover, the results of our study confirm the clinical evidence that the presence of phosphate monomers associated with air-abrasion procedures can provide more stable adhesion of resin cements to zirconia in oral conditions (Attia and Kern, 2011;Cebe et al, 2015).…”
Section: Discussionsupporting
confidence: 84%
“…Previous studies have shown that alumina with a particle size of 50 µm can be used to adjust the ceramic surface by sandblasting it at an operating distance of 0.25 MPa. Increasing the surface roughness to improve the bond strength yielded results similar to those reported in this study [34,35].…”
Section: Evaluation Of Bonding Strength and Aging Testsupporting
confidence: 85%